The family caregivers' needs on care at home with severe traumatic brain injury survivors: a review - Mohamed Ludin, Salizar; Othman, Hamidah (Lincoln University College, Asia Pacific Higher Learning Sdn Bhd, 2019)
This paper aims to review the literature with regards to the family caregivers of severe traumatic brain injury survivors and their needs for care at home. The search started by finding the relevant keywords from EBSCOhost: MeSH database. There were many related studies found by searching the following multiple databases. They are from Evidence Based Medicine (EBM) reviews @ Ovid, Journal @ Ovid Full text, Medline with Full text via EBSCOhost, CINAHL Plus with Full Text, Science Direct, and Google scholars' articles. The search terms were limited to publications ranging from 2010 to 2016. Several points were highlighted regarding the needs of family caregivers who had been taking care of traumatic brain injury survivors. It also provided information on the needs of family caregivers in terms of care, traumatic brain injury, TBI survivor complications, family caregiver's burden, caregiver challenges and the impact of traumatic brain injury to family caregiver's quality of life. Overall, the study shows that family caregivers face significant challenges toward care of TBI survivors. The review highlighted the support needed from the family caregivers, and other important facts about severe traumatic brain injury in order to understand the condition. Further research should focus on rehabilitation efforts on traumatic brain injury survivors.